SAMOSIR (Persiapan Menyongsong Bayi Baru Lahir): Optimalisasi Dalam Meningkatkan Pengetahuan Ibu Hamil Tentang Perawatan Bayi Baru Lahir - Veronica Yeni Rahmawati; Jehan Puspasari; Dian Fitria (Pusat Riset dan Inovasi Nasional, 2023)
The problems that occur in newborn babies cannot be separated from the growth and development disorders that newborn babies are susceptible to. Proper handling and care is needed by mothers who will care for newborn babies at home. If the baby receives poor care, it can pose a risk to the baby which in turn triggers problems in the newborn. The aim of this community service is to increase pregnant women's knowledge regarding newborn care. This method of community service is through an educational package that recognizes the physiology of the newborn baby's body, proper breastfeeding and the mother's psychology during pregnancy and after birth. The results of this community service before being given education, the level of knowledge was poor at 62.5%, then after being given education, the level of good knowledge was 87.5%. This shows an increase in knowledge after being given education on newborn care.